(untitled) - Moulder, Frances V. (Cambridge, 1977)
This book introduce about economy and society in Ch'ing China and Tokugawa Japan. China and Japan in the nineteeth-century. Incorporation, development, and underdevelopment.
Keywords: Phát triển kinh tế,Economic development; Khía cạnh xã hội,Social aspects